2015
DOI: 10.1016/j.neuropharm.2015.02.007
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological characterization of mGlu1 receptors in cerebellar granule cells reveals biased agonism

Abstract: The majority of existing research on the function of metabotropic glutamate (mGlu) receptor 1 focuses on G protein-mediated outcomes. However, similar to other G protein-coupled receptors (GPCR), it is becoming apparent that mGlu1 receptor signaling is multi-dimensional and does not always involve G protein activation. Previously, in transfected CHO cells, we showed that mGlu1 receptors activate a G protein-independent, β-arrestin-dependent signal transduction mechanism and that some mGlu1 receptor ligands wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
22
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 44 publications
3
22
0
Order By: Relevance
“…Third, the convergence of G protein- and β-arrestin-mediated pathways on common downstream effectors, especially MAPK and Src kinases, likely obscured contributions from β-arrestin signalling in some experimental models. Fourth, the group I mGluR agonist DHPG appears to preferentially activate G protein signalling while minimally stimulating β-arrestin pathways downstream of mGlu1 receptors3738, which could also account for the divergence between DHPG- and synaptic stimulation-induced effects observed in our studies. It will be of interest to determine what roles β-arrestins have in other forms of G protein-independent signalling by mGluRs that have been described in hippocampal pyramidal cells235, hippocampal interneurons4 and cerebellar interneurons6.…”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations
“…Third, the convergence of G protein- and β-arrestin-mediated pathways on common downstream effectors, especially MAPK and Src kinases, likely obscured contributions from β-arrestin signalling in some experimental models. Fourth, the group I mGluR agonist DHPG appears to preferentially activate G protein signalling while minimally stimulating β-arrestin pathways downstream of mGlu1 receptors3738, which could also account for the divergence between DHPG- and synaptic stimulation-induced effects observed in our studies. It will be of interest to determine what roles β-arrestins have in other forms of G protein-independent signalling by mGluRs that have been described in hippocampal pyramidal cells235, hippocampal interneurons4 and cerebellar interneurons6.…”
Section: Discussionmentioning
confidence: 81%
“…However, it is also possible that DHPG activation of non-synaptic group I mGluRs led to induction of LTD via a divergence of signalling mechanisms compared with those regulated by PP-LFS. In contrast to DHPG, quisqualate, and ACPD, glutamate and aspartate elicit ‘balanced' G protein and arrestin responses, whereas succinate and glutarate were identified as arrestin-‘biased' agonists3738. We also attempted to test if the putative arrestin-biased agonist succinate altered mf-CA3 EPSCs, but 1 mM succinate application had no effect on mfEPSC amplitudes evoked at basal frequency or on the potentiation of EPSCs induced by PP-LFS (Supplementary Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Biased agonism offers the opportunity to design drugs that are tailored to activate the desired complement of receptor responses linked to therapeutic outcomes while avoiding those linked to adverse effects. Biased agonism is operative for orthosteric agonists at the related Group I mGlu 1 receptor between G-protein and β-arrestin pathways in both recombinant and natively expressing cells (Emery et al, 2010; Emery et al, 2012; Hathaway et al, 2015). Several studies have suggested that mGlu 5 biased agonism may be linked to distinct physiological responses (Gregory et al, 2013a; Gregory et al, 2012; Noetzel et al, 2013; Zhang et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, in this case, activation of both mGlu 1 and mGlu 5 receptors was required for full activation of the current; when applied separately, both LY367385 (mGlu 1 antagonist) and MPEP (mGlu5 antagonist) significantly reduced the Group I mGlu receptor current. DHPG has been reported to be a biased toward the canonical G-protein/PCL/IP 3 pathway compared to glutamate (Emery et al 2012;Hathaway et al 2015). This may explain some of the differences observed when receptors are stimulated with DHPG versus synaptic glutamate.…”
Section: Trpc Channelsmentioning
confidence: 99%